Straightforward Synthesis of Purine 4'-Alkoxy-2'-deoxynucleosides: First Report of Mixed Purine-Pyrimidine 4'-Alkoxyoligodeoxynucleotides as New RNA Mimics - Petrová, Magdalena; Páv, Ondřej; Buděšínský, Miloš; Zborníková, Eva; Novák, Pavel; Rosenbergová, Šárka; Pačes, Ondřej; Liboska, Radek; Dvořáková, Ivana; Šimák, Ondřej; Rosenberg, Ivan (Organic letters, 2015)
Purine and pyrimidine 4'-alkoxy-2'-deoxynucleosides were efficiently prepared from nucleoside 4'-5'-enol acetates in three steps by N-iodosuccinimide promoted alkoxylation, hydrolysis, and reduction followed by conversion to phosphoramidite monomers for the solid-phase synthesis of the oligonucleotides. Fully modified 4'-alkoxyoligodeoxynucleotides, which are characterized by a prevalent N-type (RNA-like) conformation, exhibited superior chemical and nuclease resistance as well as excellent hybridization properties with a strong tendency for RNA-selective hybridization, suggesting a potential application of 4'-alkoxy-oligodeoxynucleotides in antisense technologies.
Keywords: puriny; molekulární struktura; konformace nukleové kyseliny; hybridizace nukleových kyselin; oligodeoxyribonukleotidy; Molecular Conformation; Oligodeoxyribonucleotides; sukcinimidy; Nucleic Acid Conformation; Purines; Nucleic Acid Hybridization; Succinimides; antisense oligonukleotidy; molekulární konformace; Oligonucleotides, Antisense; RNA; Molecular Structure